Pengaruh Umur, Pendidikan dan Pendapatan Terhadap Niat Beli Konsumen pada Produk Kosmetik The Body Shop di Kota Denpasar - Mahendra, Made Mahesa; Sri Ardani, I Gusti Agung Ketut (E-Jurnal Manajemen, 2015)
Change in the marketing field radically like change on techonology, globalization, government regulation. This situation and condition will arise new consumer behavior that reflected at their need and willing. In order to win the competition the marketer should quick response to the request change, to satisfy all costumer need and willing because base of marketing is customer oriented. This study aims to find out the effect of age, education and income toward consumer buy intention. Number of sample was 100 respondent with purposive sampling method. Data collection was conducted through interview and questoner. Analysis technique was multiple regression analysis. The result shows age, education, and income have significant effect toward consumer buy intention.
Keywords: Umur; Pendidikan; Pendapatan; Niat Beli Konsumen.